Pengaruh Berbagi Pengetahuan (Knowledge Sharing) Dan Komitmen (Commitment) Terhadap Kinerja Guru Pada MTs negeri Polewali I Mandar - Najma, Najma; Mandasari, Nur Fitriayu; Qamariah, Nur; Fitriani, Nur (Jurnal Manarang Manajemen dan Bisnis, 2022)
This research was conducted at the public MTs School Polewali I Mandar. The total population in this study was 68 and all populations were sampled so that the sample in this study amounted to 68 people. This study uses a questionnaire to collect data and has passed the validity and reliability test stages while data analysis uses multiple linear regression analysis normality test, multicollinearity test and coefficient of determination test and T test and F test. The results of the study at MTs Negeri 1 Polewali Mandar found that (1). Sharing knowledge has no effect on teacher performance because teachers do not use other people's opinions in teaching even though this method is very good for students and teachers also cannot combine several knowledge processes that can become new knowledge for students. (2). Teacher commitment Partially influence on teacher performance. Because teachers have a strong commitment to become teachers and teachers are also proud to be teachers at MTs Negeri I Polewali Mandar so they motivate themselves so that students can excel at the regional and national levels (3). Knowledge sharing and commitment have a positive and significant effect on teacher performance at the public MTs Polewali I Mandar school together. Because teachers already know that a good way to share knowledge is by interacting with students. In addition, the explanation of the material must also be precise so that students can understand the lesson, firmly to students who do not pay attention to the lesson. After that, it motivates students to be more active in learning so that they can get achievements at the district and national levels